Revisiting Amos Funkenstein's critique of Holocaust theology: a theological response. Issue 1 (2nd January 2018) - Garner, Daniel
ABSTRACT: This article examines Funkenstein's critically ignored humanist response to Holocaust theology. The author presents the first detailed critical assessment of Funkenstein's characterization of the discourse. Funkenstein's approach is problematic due to insufficient appreciation of his sources and particular ironies which emerge in his humanist position. Despite these failings, Funkenstein does offer some penetrating observations of Holocaust theology which theologians need to be aware of, especially in the context of the relationship between religion and violence. Consequently, fertile ground for dialogue is opened up between humanists and theologians tackling the philosophical and ethical issues raised by the Holocaust.